Granular cell tumor in a child: An uncommon cutaneous presentation - Deepashree Daulatabad; Chander Grover; Nadeem Tanveer; Divya Bansal (Wolters Kluwer Medknow Publications, 2016)
Granular cell tumors (GCTs) are uncommon soft tissue tumors which present as papulonodular lesions and are often diagnosed histopathologically. These usually develop in adulthood and are considered to be of Schwann cell origin. Most of the lesions are benign, but malignant lesions with poor prognosis are known to occur. We report a case of GCT in a 9-year-old girl presenting as an isolated lesion simulating an acrochordon. The histopathological and immunohistochemical evaluation showing polygonal granular cells positive for S-100 and neuron-specific enolase, and negative for cytokeratin and desmin helped clinch the diagnosis. Complete excision under local anesthesia was done. The atypical clinical morphology and diagnostic histopathology of this uncommon entity are presented to aid the clinician in recognizing it. These tumors are mostly benign, rarely malignant, with the latter category having a poor prognosis. A near-complete excision is recommended in view of the minimal risk of malignant transformation.